2011
DOI: 10.3748/wjg.v17.i15.1961
|View full text |Cite
|
Sign up to set email alerts
|

Unusual histopathological findings in appendectomy specimens: A retrospective analysis and literature review

Abstract: Although unusual pathological findings are seldom seen during an appendectomy, all appendectomy specimens should be sent for routine histopathological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
182
5
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(215 citation statements)
references
References 95 publications
23
182
5
5
Order By: Relevance
“…Although lymphoid hyperplasia and fecalith are the most common etiologic factors of acute appendicitis, some unusual factors including pinworms and tumors have been identified [1,2]. Histopathological examination of the appendectomy specimens may be relevant as it yields important clinical information in addition to operative findings [3,4]. The aim of this study was to assess the value of routine histological examination of the resected appendix.…”
Section: Introductionmentioning
confidence: 99%
“…Although lymphoid hyperplasia and fecalith are the most common etiologic factors of acute appendicitis, some unusual factors including pinworms and tumors have been identified [1,2]. Histopathological examination of the appendectomy specimens may be relevant as it yields important clinical information in addition to operative findings [3,4]. The aim of this study was to assess the value of routine histological examination of the resected appendix.…”
Section: Introductionmentioning
confidence: 99%
“…Akbulut et al, reported unusual histological findings in 54 of 5462 (1%) appendectomy specimens; 37 enterobiasis, 6 carcinoids, 4 mucinous cystadenomas, 2 eosinophilic infiltrations, 2 mucoceles, 2 tuberculosis, and 1 neurogenic hyperplasia [4]. An examination of 4545 appendectomy specimens, performed for acute appendicitis, showed 44 (0.97%) unexpected tumours of appendix including an adenocarcinoma and a primary lymphoma of the appendix [5].…”
mentioning
confidence: 99%
“…4 Oxyuriasis infestation has been reported in 4% of appendicectomy specimens. Granulomatous diseases as Tuberculosis can cause appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Appendicular Tuberculosis is reported in up to 3% of all the specimens examined. 4,5,8 Acute Appendicitis can be caused by Appendicular neoplasms with less than 50% identified intraoperatively. [1][2][3][4][5] The reported incidence of neoplasia in Appendectomy specimens is in the range of 3% 4 to 7.1%, wherease Furman etal have shown neoplasm as cause of appendicitis in 29.4% of patients undergoing interval appendicectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation